Second monotherapy in childhood absence epilepsy - Cnaan, Avital (Neurology, 2017)
OBJECTIVE: To determine optimal second monotherapy for children with childhood absence epilepsy (CAE) experiencing initial treatment failure. METHODS: Children with CAE experiencing treatment failure during the double-blind phase of a randomized controlled trial comparing ethosuximide, valproic acid, and lamotrigine were randomized to open-label second monotherapy with one of the 2 other study therapies. Primary study outcome was freedom from failure proportion at week 16–20 and month 12 visits after randomization. Secondary study outcome was percentage of participants experiencing attentional dysfunction at these visits. RESULTS: A total of 208 children were enrolled, randomized, and received second therapy. At both week 16–20 visit and month 12 visit, ethosuximide's (63%, 57%) and valproic acid's (65%, 49%) freedom from failure proportions were similar to each other and higher than lamotrigine's (45%, 36%, p = 0.051 and p = 0.062). At both time points, ethosuximide and valproic acid had superior seizure control compared to lamotrigine (p < 0.0001). At both the week 16–20 and month 12 visits, attentional dysfunction was numerically more common with valproic acid than with ethosuximide or lamotrigine. For each medication, second monotherapy freedom from failure proportions demonstrated noninferiority to initial monotherapy freedom from failure proportions. CONCLUSIONS: As second monotherapy, ethosuximide and valproic acid, demonstrated higher freedom from failure proportions and greater efficacy than lamotrigine; valproic acid was associated with more attentional dysfunction. Ethosuximide is the optimal second monotherapy for children with CAE not responding to initial therapy with other medications. CLINICALTRIALS.GOV IDENTIFIER: NCT00088452. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that for children with CAE experiencing initial treatment failure, second monotherapy with ethosuximide or valproic acid is superior to lamotrigine.